Penerapan Asas Iktikad Baik Dalam Perjanjian Jual Beli Tanah - Jafar Salam (Fakultas Hukum Universitas Mataram, 2017)
The principle of good faith in land sale agreement, especially in disputes between the seller and buyer is still limited to the execution of the contract. In court view the existence of good faith principle is not to correct the contents of the agreement, but the means to assess whether the parties have been good in fulfilling their performance or not. The court did not apply the principle of good faith to judge whether the contents of the sale agreement were fair and fair or not. Whereas in the context of the protection of a third party who obtains a good goodwill, the principle of good faith is applied selectively. A third party is deemed to have acquired a good good will if he or she does not know that it belongs to the seller. The Buyer-party benchmark is considered really do not know is not know even though it has been worthy of examination both the land letters and the physical land of the object of sale. In addition, buyers also have to find out by multiplying information from the parties who berwenag like village head, head of the hamlet, the BPN or to the court.